Oral leiomyoma extending in retromolar region - A Goel; H Goel (Wolters Kluwer Medknow Publications, 2011)
Leiomyoma is a benign smooth muscle tumor that rarely affects children and occurs most frequently in the uterine myometrium and gastrointestinal tract. Its occurrence in the oral cavity is considered rare probably because of the scarcity of smooth muscle tissue in the oral cavity. The most common intraoral sites for leiomyoma are lips, palate and tongue. The purpose of this case report is to present the clinical features, diagnosis and treatment of a rare case of oral leiomyoma in a 13-year-old girl with a 4-month history of a swelling in her left mandibular area extending from first molar to retromolar region.